Estudo sobre as morfologias da martensita formada em aços 9Ni - Gondim Júnior, José Flávio Pereira (2021)
This study aimed to evaluate low carbon steel's mechanical properties with 9% nickel, commonly called 9Ni steel, to establish a correlation with the microstructural changes observed after the quenching heat treatment under different conditions. This material is traditionally quenched and tempered at temperatures ranging from 570oC to 620oC. Heat treatments were executed under four different conditions, in order to evaluate the microstructure of the steel, especially the formation of the coarse lath martensite, as well as to correlate the influence of this microconstituent with the impact energy of these alloy under cryogenic conditions. Two samples were prepared for each condition and microstructural characterization was performed using a scanning electron microscopy from these treatments. Then, the phase mapping was performed using the EBSD technique, and the hardness and microhardness were carried out. For each five conditions were also extracted samples to carry out Charpy tests at -196oC, aiming to evaluate the material toughness and correlate it with the corresponding microstructure. The result obtained experimentally showed the presence of coarse lath martensite morphology in all quenched samples, as a phase resulting from the high cooling rate. Additionally, the presence of nanometric carbides within the coarse lath martensites has been observed, as a result of anautotempering process, due to the lower density of dislocations and long distances to the carbon diffusion. It was also possible to verify the two main characteristic morphologies of the martensitic microstructure: thin and coarse lath martensite. Toughness proved to be a property strongly influenced by quenching and, dispite the relatively higher values in the condition where coarse lath martensite's most significant presence occurred, a direct correlation between these two results was not observed.